Complement C6 deficiency protects against diet-induced atherosclerosis in rabbits - Schmiedt, Walther; Kinscherf, Ralf; Deigner, Hans-Peter; Kamencic, Huse; Nauen, Olaf; Kilo, Juliane; Oelert, Hellmut; Metz, Jürgen; Bhakdi, Sucharit (Arteriosclerosis, thrombosis, and vascular biology, 1998)
Abstract: Low-density lipoprotein (LDL) can be transformed to an atherogenic moiety by nonoxidative, enzymatic degradation. Enzymatically degraded LDL induces macrophage foam cell formation, provokes release of cytokines, and also activates complement. To determine whether complement activation may contribute to atherogenesis, 6 pairs of homozygous C6-deficient rabbits and their non-C6-deficient heterozygous siblings were fed a cholesterol-rich diet for 14 weeks. Cholesterol levels and plasma lipoprotein profiles of the animals in the C6-competent and C6-deficient groups did not significantly differ, and the high density lipoprotein and LDL cholesterol ratios at the end of the experiment were 0.07±0.01 and 0.08±0.01 (SEM), respectively. However, differences in atherosclerotic plaque formation were discernible macroscopically, with extensive aortic lesions being visible in all C6-competent animals and absent in all C6-deficient animals. Aortas were sectioned from thorax to abdomen, and 10 sections were stained from each aorta. Quantification of atherosclerotic lesions and lumen stenosis with the use of computer-based morphometry documented a dramatic protective effect of C6 deficiency on the development of diet-induced atherosclerosis. We conclude that the terminal complement sequence is centrally involved in atherosclerotic lesion progression.